Pemberdayaan Masyarakat Melalui Teknologi Akuaponik Untuk Kemandirian Pangan Di Desa Banyuresmi Kabupaten Pandeglang Provinsi Banten - Syamsunarno, Mas Bayu; Fatmawaty, Andi Apriany; Munandar, Aris; Anggaeni, Dian (Universitas Nusantara PGRI Kediri, 2020)
Banyuresmi village is a national priority rural area that is dared in Pandeglang Regency, Banten Province. Limited facilities and infrastructure, especially the lack of water supply have resulted in a lack of carrying capacity for economic growth based on local potential. Banyuresmi Village Community also has not been able to manage natural resources optimally. Optimization of natural resources can be done in an integrated manner in the yard of the house through aquaponics technology. The application of aquaponics technology can be used as a solution to the problems found in Banyuresmi Village so that the food needs of its citizens can be fulfilled so that the creation of food independence. Community service activities include increasing knowledge of aquaponic technology through training and implementation of aquaponic cultivation. The implementation of community service activities uses the Participatory Rular Appraisal (PRA) method, Participatory Technology Development (PRD), persuasive and educative approaches. The results of knowledge measurement showed an increase in knowledge, incorporation of cultivation, and fertilization with fish droppings to 65-70%. Catfish harvest in aquaponic cultivation reaches 91 kg with a maintenance period of 3 months. Besides fish, harvest vegetables such as kale, baby romaine, cuisine, and lettuce.